Centralization vs Flexibility: Comparative Study of Education Policy in Sudan and Vietnam - Saifaldin Onia (Journal of Social Studies and Education, 2025)
This study comparatively analyzes national education policies in Sudan and Vietnam to understand the structural and institutional differences in the education systems of the two countries. Using a qualitative approach of comparative case studies, data is collected through studies of official documents, reports of international institutions, and academic literature. The analysis was conducted through a thematic-based content analysis, which encompassed the structure of the education system, language and curriculum policies, as well as quality strategies and the role of institutions. The results show that Sudan implements a fully centralised model with strict central government control over all aspects of policy, including a uniform curriculum and language of instruction (Arabic), with no room for local innovation. In contrast, Vietnam implements a centralised policy model with flexible implementation, leaving room for adaptation at the school and university levels. The structure of Vietnam's education system is more adaptable, supported by a bilingual policy (Vietnamese and English), as well as a comprehensive quality strategy that includes improved budgets, teacher quality, and institutional autonomy. This study suggests that differences in institutional approaches have a significant impact on the effectiveness of implementation and innovation in education.